Lipase and Its Unique Selectivity: A Mini-Review - Jun-Young Park; Kyung-Min Park (Journal of Chemistry, 2022)
Contrary to other solid catalysts, enzymes facilitate more sophisticated chemical reactions because most enzymes specifically interact with substrates and release selective products. Lipases (triacylglycerol hydrolase, EC 3.1.1.3), which can catalyze the cleavage and formation of various acyl compounds, are one of the best examples of enzymes with a unique substrate selectivity. There are already several commercialized lipases that have become important tools for various lipid-related studies, although there is still a need to discover novel lipases with unique substrate selectivity to facilitate more innovative reactions in human applications such as household care, cosmetics, foods, and pharmaceuticals. In this mini-review, we focus on concisely demonstrating not only the general information of lipases but also their substate selectivities: typoselectivity, regioselectivity, and stereoselectivity. We highlight the essential studies on selective lipases in terms of enzymology. Furthermore, we introduce several examples of analysis methodology and experimental requirements to determine each selectivity of lipases. This work would stress the importance of integrating our understanding of lipase chemistry to make further advances in the relevant fields.